Tax expenditures in OECD countries (OECD, 2010)
In all OECD countries, governments collect revenues through taxes and redistribute this public money, often by obligatory spending on social programs such as education or health care. Their tax systems usually include "tax expenditures" - provisions that allow certain groups of people, such as small businessmen, retired people or working mothers, or those who have undertaken certain activities, such as charitable donations, to pay less in taxes. The use of tax expenditures by governments is pervasive and growing. At a time when many government budgets are threatened by population aging and adverse cyclical developments, there is a pressing need to avoid inefficient government programs, some of which may utilize tax expenditures. This book sheds light on the use of tax expenditures, mainly through a study of ten OECD countries: Canada, France, Germany, Japan, Korea, Netherlands, Spain, Sweden, the United Kingdom and the United States; it highlights key trends and successful practices, and addresses a broad range of government finance issues, including tax policy making, tax and budget efficiency, fiscal responsibility and rule making.--Publisher's description